Peningkatan Aktivitas Belajar Siswa dengan Menggunakan Media Power Point di Kelas IV SDIT Wisata Hasanah - Ardianti, Selvi; Halidjah, Siti; Kresnadi, Hery (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to describe the increase in student learning activities by using power point media in class IV SDIT Wisata Hasanah. The research method used is action research with the form of collaborative classroom action research. The research subjects were 24 students consisting of 9 boys and 15 girls and the fourth grade teacher of SDIT Wisata Hasanah. The data collection technique used was observation. Data collection tools in the form of observation sheets. This research was conducted over three cycles. The results of this study include: the teacher's ability to carry out learning in cycle I average value of 7.8 (good category), cycle II increased with an average value of 8.5 (good category), and cycle III increased with an average value of 8.9. The results of research on student learning activities in cycle I obtained an average percentage of 65.61%, cycle II increased by obtaining an average percentage of 82.58%, and in cycle III increased with an average percentage of 87.15%. Based on the results of research data and analysis, it shows that using power point media can increase student learning activities in class IV SDIT Wisata Hasanah.